Limosilactobacillus reuteri Y15 enhances uterine development and function in gilts via the gut-uterus axis - Juanli Huo; Shen Li; Dongxin Lu; Lei Li; Weidong Zhang; Yukang Li; Bin Yao; Yong Zhao; Yawei Zhang; Jie Zhang; Huiying Luo (Theriogenology, 2026)

Rhizosphere reactive oxygen species as a protective barrier suppress Fusarium oxysporum invasion in tomato - Yaru Zhu; Huiqiang Yang; Siqi Shen; Meng Liu; Zelin Hao; Yawei Zhou; Jinbo Liu; Hanzhong Jia (Environmental Chemistry Letters, 2026)

The Priming Impacts of Early Hypoxia Exposure in Abalone Parents Are Transmitted to Offspring - Yawei Shen; Yue Dai; Qizhen Xiao; Miaoqin Huang; Xuan Luo; Caihuan Ke; Weiwei You (Molecular Ecology, 2026)
The early environmental disturbances may have lasting effects on the sensitivity and acclimation abilities of organisms in later life stages or even in subsequent generations. However, measuring the responses of marine species with long generation times across multiple generations is challenging. Here, we investigated the inter‐generational carryover effects of early hypoxia exposure on Pacific abalone ( Haliotis discus hannai ), which takes two years to reach reproductive maturity. A five‐year study revealed that embryonic hypoxia exposure in abalone parents (F 0 ) has long‐lasting effects, which makes offspring (F 1 ) have higher specific growth rates and hypoxia tolerance despite these offspring having never been exposed to hypoxia. Embryonic hypoxia exposure did not reduce the genetic diversity ( Na , Ne , I , Ho , He and F ) of abalone between two generations, nor did it result in genetic differentiation ( F st and Nei's genetic distance) within a single generation. However, natural selection during the two‐year culture period may have favoured F 0 individuals with superior fitness traits to survive, ultimately driving genetic divergence among the F 1 generation. Furthermore, differentially expressed genes (e.g., mthfr and shmt1 ) that reflect the single‐generational, inter‐generational, and multi‐generational effects were involved in methylenetetrahydrofolate reductase activity and one carbon pool by folate. These genes might mediate the process by which F 0 embryonic hypoxia exposure alters the adaptive traits of the F 1 generation. This study revealed that the priming impacts of early hypoxia exposure might persist across generations through both genetic and non‐genetic mechanisms, providing insights for protecting marine organisms under global climate change.

Bisphenol A promotes esophageal carcinogenesis by activating the MMP1–PCOLCE regulatory axis and remodeling the tumor immune microenvironment - Yawei Cui; Guohang Shen; Huiling Chen; Ruoyan Wang; Chengping Zhang; Lu Han; Kaiyong Wang; Yang Chen; Junfeng Li; Xia Gao; Yupei Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrated Heart Rate Monitoring and Transcriptomic Analyses Reveal Distinct Responses to Hypo- and Hypersalinity Stress in Abalone - Nan Chen; Run Hu; Yun Chen; Weiwei You; Caihuan Ke; Yawei Shen (Fishes, 2026)
In the context of global climate change, intensified salinity fluctuations driven by altered precipitation, extreme rainfall events, and typhoons have emerged as a major threat to coastal mollusk aquaculture. In this study, integrated physiological and transcriptomic analyses were performed to investigate the responses of Pacific abalone (DD, Haliotis discus hannai) and its hybrid (DF, H. discus hannai ♀ × H. fulgens ♂) to hypo- and hypersalinity stress. Two salinity breakpoints (BPS1 for hyposalinity, BPS2 for hypersalinity) were identified using heart rate monitoring to indicate the osmotic tolerance thresholds of the abalone. The BPS1 and BPS2 values did not differ significantly between the DD and DF groups. However, a subsequent 30-day culture trial confirmed that exposure to the salinity level corresponding to BPS1 significantly reduced growth and survival of both DD and DF groups. To explore the molecular mechanisms underlying these two salinity breakpoints in abalone, the transcriptomes of hemocytes and gill tissues were profiled under both stress conditions. Both hypo- and hypersalinity stress induced pronounced transcriptomic responses in abalone, accompanied by upregulated differentially expressed genes (DEGs) significantly enriched in pathways like TNF and NF-κB signaling, including genes like piap, diap2, birc7-a, birc2, and birc3. However, abalone exhibited more intense responses to hypersalinity stress, as reflected by a greater number of annotated differentially expressed genes (DEGs) and more complex transcriptional regulation. Overall, this study integrates physiological assessment based on heart rate monitoring, aquaculture trials, and transcriptomic analysis to advance our mechanistic understanding of osmotic stress adaptation in abalone, while laying a scientific foundation for the sustainable development of abalone aquaculture under global climate change.

Investigating the impact of different abuse methods on the thermal runaway behavior of lithium batteries under high-rate charge and discharge conditions - Yajun Huang; Weifeng Xu; Xiongqi Shen; Yinquan Zhao; Yang Cao; Wei Bai; Junling Wang; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2026)

A methodical comparative analysis of the improved dechlorination of trichloroethylene (TCE) using C-, N-, and S-modified zero-valent iron (ZVI) - Xiang Luo; Hongwei Chen; Hongjian Shen; Ling Zhang; Jinbo Chen; Shuai Liu; Bo Gao; Honglei Zhang; Yawei Gu (Journal of Water Process Engineering, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Applications of machine learning-based quantitative structure activity relationship (ML-QSAR) models in environmental science - Chao Chen; Yujia Tan; Yawei Liu; Miaomiao Sun; Zhiquan Wang; Xiangyong Zheng; Zhemin Shen; Min Zhao (Environmental Research, 2026)

Nanopolystyrene and chrysene-induced gill damage in fish - Rahma Sakina Said Aly; Yawei Shen; Jinliang Zhao; Tiantian Chen; Xiaowu Chen (Aquaculture, 2026)

Corrigendum to “Genomic and functional characterization of the lect2 gene from Siniperca chuatsi” [Fish Shellfish Immunology 107 (2020) 146–155] - Yawei Shen; Ming Cao; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen; Yanhui Bi (Fish & Shellfish Immunology, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

Phase-resolved multi-path drivers of PM2.5 evolution in eastern China under Clean Air Actions and carbon neutrality scenarios - Yasong Li; Lili Shen; Dandan Wei; Tijian Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie; Yanjin Wang (Journal of Hazardous Materials, 2026)

Brine-filled MXene “Sandwich” system for synergistically enhanced electrochemical energy storage and solar desalination - Bowen Liu; Xuedong He; Yawei Yang; Yuyao Shen; Yihong Liu; Qi Zhao; Xinye Xu; Mo Zhou; Tianyi Wang; Wenxiu Que (Chemical Engineering Journal, 2026)

Morphological and functional analysis of saccus vasculosus of mandarin fish ( Siniperca chuatsi ) - Rahma Sakina Said Aly; Jiajie Fang; Keying Li; Xiao Ma; Jiong Gao; Meng Zhang; Xiaowu Chen; Yawei Shen (Journal of Fish Biology, 2026)
The saccus vasculosus (SV) is a specialized periventricular organ found in some species of teleost and elasmobranch fishes, located at the back of the hypothalamus and pituitary gland. However, its function remains incompletely understood. In this study, histological, transmission electron microscopy (TEM) and transcriptomic analyses were employed to investigate the SV of the mandarin fish ( Siniperca chuatsi ) to gain insights into its morphology, gene expression profile and function. Through histological staining techniques, different cell types within the SV can be identified and characterized. The SV is highly folded vascularized neuroepithelium and is deeply connected to blood vessels. TEM studies showed that the capillaries that produced the lumen formed complex narrow channels are linked to the third ventricle of the hypothalamus. The bright neuroepithelium is formed by coronet cells and supporting glial cells, interspersed with liquor‐containing neurons, while the dark contrast is attributed to the presence of heavy elements such as calcium. We identified 28 specific genes in SV, which are most enriched in the purine metabolism pathway, including the genes of pde9al , pde9ac , pde6hl and sgc88el . Gene Ontology biological process analysis for the SV‐specific genes showed that response to osmotic stress was the hub term according to the enrichment maps. Additionally, SV‐specific genes opsin ( opsin8b ), photoreceptor ( pcare1 ) and aquaporin ( aqp4 , aqp9l ) of Siniperca chuatsi may indicate that they play a role as a sensor of season and are involved in osmoregulation. This study, the first on the Siniperca chuatsi , suggests that the SV may have unique physiological functions in teleost fish.

A multi-target QSAR model for simultaneously predicting the rate constants of reactions across multiple oxidation systems - Yawei Liu; Zhiquan Wang; Xiangyong Zheng; Min Zhao; Zhemin Shen (Journal of Hazardous Materials, 2025)

Transcriptome to reveal the immunological defenses in mandarin fish (Siniperca chuatsi) skin with LPS and poly (I:C) infection - Yawei Shen; Jiong Gao; Meng Zhang; Yongjing Li; Rahma Sakina Said Aly; Lei Wang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Xiaowu Chen (Fish & Shellfish Immunology, 2025)

Energy-force coupling in interfacial solar vapor generation: A pathway to sustainable salt management - Yihong Liu; Yawei Yang; Bowen Liu; Qi Zhao; Yuyao Shen; Mengyuan Qiang; Yong Ma; Wenxiu Que (Desalination, 2025)

Seasonal variation in two culture systems and genome-wide association analysis of taurine content in the foot muscles of the Pacific abalone (Haliotis discus hannai) - Ziheng Yin; Junyu Liu; Wenchao Yu; Yawei Shen; Yang Gan; Yexin Chen; Jinwei Ke; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

Investigation on the inhibition mechanism of thermal runaway propagation in high-rate cycling lithium-ion pouch cells - Yajun Huang; Xiongqi Shen; Yinquan Zhao; Junling Wang; Yang Cao; Wei Bai; Yu Fan; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2025)

Synergy of bismuth and tungsten in Bi2WO6 for PMS activation to enhance degradation of ammonium dibutyl dithiophosphate in flotation wastewater - Mingwei Shen; Teng Wang; Yawei Wang; Zhiyuan Li; Jiayou Liu; Ke Jin; Hesheng Yu (Journal of Water Process Engineering, 2025)

Genome-wide association study reveals growth-related mutations and candidate genes at early growth stages in largemouth bass (Micropterus salmoides) - Xiao Ma; Dongcai Chen; Zhilin Jia; Yue Xu; Zhigang Qiao; Lei Wang; Hongxia Jiang; Miao Yu; Yongjing Li; Xiaotian Gao; Chunlong Zhao; Yawei Shen; et al. (Aquaculture, 2025)

Theoretical calculation on degradation mechanism of novel copolyesters under CALB enzyme - Yuanyang Ren; Zhiwen Cheng; Luwei Cheng; Yawei Liu; Mingyue Li; Tao Yuan; Zhemin Shen (Journal of Environmental Sciences, 2025)

Genome-wide association analysis study on host resistance against the Aeromonas veronii of largemouth bass Micropterus salmoides - Meng Zhang; Xiao Ma; Zerui Wang; Yuqing Han; Zhilin Jia; Dongcai Chen; Yue Xu; Zhigang Qiao; Xinyu Jiang; Lei Wang; Hongxia Jiang; Miao Yu; et al. (Fish & Shellfish Immunology, 2025)

Transcriptome analysis of hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂) reveals non-additive effects contributing to growth heterosis at early summer water temperature in Fujian - Zekun Huang; Yawei Shen; Xingze Wang; Qizhen Xiao; Yi Wang; Yang Gan; Zhaofang Han; Wanbo Li; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

A comprehensive screening method of oxidation systems based on reaction rate constant (k value) and emergy (Em value) - Yawei Liu; Zhiquan Wang; Zhiwen Cheng; Yuanyang Ren; Yujia Tan; Tao Yuan; Zhemin Shen (Science of The Total Environment, 2025)

The weak association between hypoxia tolerance and thermal tolerance increases the susceptibility of abalone to climate change - Yawei Shen; Yue Dai; Feng Yu; Wenzhu Peng; Junyu Liu; Weiwei You; Xuan Luo; Caihuan Ke; Nan Chen (Environmental Research, 2025)

Carryover effects of embryonic hypoxia exposure on adult fitness of the Pacific abalone - Yue Dai; Yawei Shen; Caihuan Ke; Xuan Luo; Miaoqin Huang; Huoqing Huang; Weiwei You (Environmental Research, 2024)

Optimal conditions for cryopreservation by vitrification of largemouth bass (Micropterus salmoides) embryos - Meng Zhang; Xiao Ma; Yuqing Han; Zerui Wang; Zhilin Jia; Dongcai Chen; Zhigang Qiao; Xiaotian Gao; Chunlong Zhao; Yawei Shen (Animal Reproduction Science, 2024)

Short time-series expression transcriptome data reveal the gene expression patterns and potential biomarkers of blood infection with LPS and poly (I:C) in Mandarin fish (Siniperca chuatsi) - Yawei Shen; Rahma Sakina Said Aly; Tiantian Chen; Hewei Jiang; Yufei Liu; Yongxiang Wang; Xiaowu Chen (Fish & Shellfish Immunology, 2024)

A high throughput method to assess the hypoxia tolerance of abalone based on adhesion duration - Yue Dai; Yawei Shen; Yanbo Liu; Weiwei Xia; Jiawei Hong; Yang Gan; Jie Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2024)

The silent threat: Nanopolystyrene and chrysene pollutants disrupt the intestinal mucosal barrier, new insights from juvenile Siniperca chuatsi - Tiantian Chen; Rahma Sakina Said Aly; Yawei Shen; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Science of The Total Environment, 2024)

Pollution levels and probability risk assessment of potential toxic elements in soil of Pb–Zn smelting areas - Mingyue Li; Jinyang Zhou; Zhiwen Cheng; Yuanyang Ren; Yawei Liu; Linling Wang; Liu Cao; Zhemin Shen (Environmental Geochemistry and Health, 2024)

Nanoplastics and chrysene pollution: Potential new triggers for nonalcoholic fatty liver disease and hepatitis, insights from juvenile Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yaoji He; Yawei Shen; Zequn Huang; Yifeng Gu; Qun Wei; Jinliang Zhao; Xiaowu Chen (Science of The Total Environment, 2024)

Histopathological, physiological, and multi-omics insights into the hepatotoxicity mechanism of nanopolystyrene and/or diclofenac in Mylopharyngodon piceus - Tiantian Chen; Hewei Jiang; Yaoji He; Yawei Shen; Jiajie Fang; Zequn Huang; Yubang Shen; Xiaowu Chen (Environmental Pollution, 2024)

An overview of the mechanisms underlying hypoxia tolerance differences in aquatic animals and their inspirations for aquaculture - Yawei Shen; Weiwei You; Xuan Luo; Ying Lu; Miaoqin Huang; Caihuan Ke (Reviews in Fish Biology and Fisheries, 2023)

Impacts of exposure to nanopolystyrene and/or chrysene at ambient concentrations on neurotoxicity in Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yawei Shen; Tingwen Cui; Zonglin Yang; Yufei Liu; Jinliang Zhao; Xiaowu Chen (Chemosphere, 2023)

Development of near-infrared reflectance spectroscopy (NIRS) model and genome-wide association study for glycogen and protein content in Pacific abalone - Junyu Liu; Muzhi Zhou; Ziheng Yin; Dan Huang; Liyan Zhu; Weiguang Zou; Wenchao Yu; Yawei Shen; Zekun Huang; Weiwei You; Caihuan Ke; Xuan Luo (Aquaculture, 2023)

Prenatal polymetallic exposure and small for gestational age: A case-control study in Taiyuan, China - Zhitong Shen; Yue Lu; Zexin Song; Jinbo Li; Wangjun Li; Shan Li; Mengru Wang; Yongliang Feng; Suping Wang; Yawei Zhang; Weiwei Wu (Journal of Trace Elements in Medicine and Biology, 2023)

Supplementation with Akkermansia muciniphila improved glucose metabolism disorder in common carp (Cyprinus carpio L.) - Guokun Yang; Aixia Jiang; Huimin Cai; Fu You; Shengkui Wu; Yanmin Zhang; Xindang Zhang; Yawei Shen; Xulu Chang; Wenpan Hu; Keke Li; Xiaolin Meng (Aquaculture, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Overview of the main biological mechanisms linked to changes in periodontal ligament stem cells and the inflammatory microenvironment - Xuetao Zhao; Hongbing Lin; Tong Ding; Yawei Wang; Na Liu; Yuqin Shen (Journal of Zhejiang University-SCIENCE B, 2023)

Genotype by environment interactions in feed efficiency of Pacific abalone (Haliotis discus hannai) reared at different water temperatures - Wenchao Yu; Yawei Shen; Junyu Liu; Weiguang Zou; Zekun Huang; Miaoqin Huang; Ying Lu; Jinwei Ke; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2023)

Genome-wide association and transcriptome studies reveal the segregation mechanism of mantle markings in three-way cross hybrid abalone - Qizhen Xiao; Shihai Gong; Yawei Shen; Yisha Lu; Xinlian Lai; Wenzhu Peng; Zekun Huang; Zhaofang Han; Hongjing Ji; Yang Gan; Xuan Luo; Weiwei You; et al. (Frontiers in Marine Science, 2022)
Trait separation which often appears in shellfish progeny, has been commercially used in shellfish breeding projects. A three-way cross hybrid abalone was produced with heterosis in growth performance and thermal tolerance, and with segregation in mantle marking. However, the inheritance mechanism of mantle marking is unclear. In this study, mantle marking was demonstrated to be a qualitative trait, following simple Mendelian inheritance, through inheritance pattern analysis of the presence of black markings on the mantle in five families of three-way cross of hybrid abalone. Thermal tolerance of abalone was assessed by the Arrhenius breakpoint temperature (ABT) of cardiac performance and a correlation between mantle marking and thermal tolerance of abalone was verified. A genome-wide association study (GWAS) for mantle marking was conducted using 603,067 high-quality single nucleotide polymorphisms (SNPs) derived from 57 individuals with mantle markings (Y group) and 58 individuals without mantle markings (N group). A total of 493 SNPs that were significantly ( p < 2.32E–07) associated with mantle markings were mainly distributed on chromosome 15. In the potential significantly associated region, 80 genes, including pigmentation-related genes PTPRT , PTPRC , PNCA , and CALM4 were annotated. Transcriptome analysis of the two groups showed that the expression levels of these genes ( PTPRT , DDT-b , ATOX1 , SLC6A3 , and GSTO1 ) were significantly different, and they may play important roles in the formation of mantle markings in the three-way cross hybrid abalone. Overall, our data provide valuable information for deciphering the phenotype differences of mantle marking in three-way cross hybrid abalone and help in the molecular marker-assisted breeding in abalone.

Research on Surrounding Rock Control Technology of Gob-Side Entry Retaining by Directional Roof Cutting in a Deep Coal Mine - Haojie Xue; Shibao Shen; Haoran Lu; Renbao Zhao; Peishuai Li; Yawei Zhao; Qibin Jiang; Longjiang Wang; Beizhan Fan; Tao Qin (Geotechnical and Geological Engineering, 2022)

Fluctuations in the heart rate of abalone in response to low salinity stress - Grace Afumwaa Boamah; Feng Yu; Yawei Shen; Weiwei You; Changan Xu; Xuan Luo; Caihuan Ke (Aquaculture International, 2022)

Promoter methylation and expression of the rassf4 gene in Nile tilapia ( Oreochromis niloticus ) - Yawei Shen; Huiyang Li; Min Zhou; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Journal of Fish Biology, 2021)
Oreochromis niloticus RAS‐association domain family 4 ( rassf4 ) was specifically expressed in the ovaries. Immunohistochemistry results showed that Rassf4 was located in follicular cells. The methylation percentages of the promoter region (−734/−1012) of rassf4 in the ovaries and testes were 13.28% and 92.85%, respectively. Deleting the fragment of −734 to −1012 sites significantly reduced the basal activity of the rassf4 promoter to 62.33%, which indicated that this region was important for the transcription of the rassf4 gene. This study lays the foundation for further research on the function of fish rassf4 .

Two-dimensional transition metal phthalocyanine sheet as a promising electrocatalyst for nitric oxide reduction: a first principle study - Shiqiang Liu; Yawei Liu; Zhiwen Cheng; Xiaoping Gao; Yujia Tan; Zhemin Shen; Tao Yuan (Environmental Science and Pollution Research, 2021)

Expression profile analyses of mettl8 in Oryzias latipes - Wei Pang; Ziwei Zhao; Yawei Shen; Yanhui Bi; Yifeng Gu; Xiaowu Chen (Fish Physiology and Biochemistry, 2020)

Irf3 from mandarin fish thymus initiates interferon transcription - Xiaowu Chen; Yawei Shen; Minglin Wu; Jinliang Zhao (Fish Physiology and Biochemistry, 2019)

LC–MS/MS-Based Metabolome Analysis of Biochemical Pathways Altered by Food Limitation in Larvae of Ivory Shell, Babylonia areolata - Jingqiang Fu; Minghui Shen; Yawei Shen; Wengang Lü; Miaoqin Huang; Xuan Luo; Jinjin Yu; Caihuan Ke; Weiwei You (Marine Biotechnology, 2018)

SNP detection by parallel targeted sequencing from degraded DNA samples in Haliotis diversicolor - Peng Ren; Yawei Shen; Zekun Huang; Miaoqin Huang; Xuan Luo; Jin-Chywan Gwo; Caihuan Ke; Weiwei You (Conservation Genetics Resources, 2017)

Genotype frequency and F ST analysis of polymorphisms in immunoregulatory genes in Chinese and Caucasian populations - Qing Lan; Min Shen; Dino Garcia-Rossi; Stephen Chanock; Tongzhang Zheng; Sonja I. Berndt; Vinita Puri; Guilan Li; Xingzhou He; Robert Welch; Shelia H. Zahm; Luoping Zhang; et al. (Immunogenetics, 2007)

Genetic polymorphisms in the oxidative stress pathway and susceptibility to non-Hodgkin lymphoma - Qing Lan; Tongzhang Zheng; Min Shen; Yawei Zhang; Sophia S. Wang; Shelia H. Zahm; Theodore R. Holford; Brian Leaderer; Peter Boyle; Stephen Chanock (Human Genetics, 2007)

Polymorphisms in DNA repair genes and risk of non-Hodgkin lymphoma among women in Connecticut - Min Shen; Tongzhang Zheng; Qing Lan; Yawei Zhang; Shelia H. Zahm; Sophia S. Wang; Theodore R. Holford; Brian Leaderer; Meredith Yeager; Robert Welch; Daehee Kang; Peter Boyle; et al. (Human Genetics, 2006)